ASSOCIATION OF POLYMORPHISMS OF THE PPAR FAMILY GENES AND UCP2 GENE WITH ECHOCARDIOGRAPHY INDICES IN ATHLETES - Polishchuk, A.O.; Drozdovska, S.B.; Hrubyak, L.M.; Dolzhenko, M.M.; Dosеnkо, V.E. (World of Medicine and Biology, 2021)
Development of myocardium hypertrophy in athletes due to systematic physical training is multifactorial process vastly genetically determined. In this work, we studied DNA polymorphism and cardiac hypertrophy in professional athletes under physical activity with aerobic mode of energy supply. We have found that a group of athletes with hypertrophic alteration of the myocardium was characterized with increased frequency of the G/A gene polymorphism of PPARGC1A gene comparing to a group of athletes without pronounced changes of heart structure. The correlation between some polymorphism of genes and indices of echocardiography study was established: the correlation between G/C polymorphism of the PPARA gene and the middle septum thickness; correlation between Pro/Ala polymorphism of the PPARG gene and the left ventricular end-diastolic volume. By the method of binary logistic regression, a model for prognosis of effect on hypertrophy was established – 68.2 % including two polymorphisms: PPARG and UCP2.
Keywords: DNA polymorphism; myocardium hypertrophy; echocardiography; adaptation to physical load